2021
DOI: 10.1097/sla.0000000000005116
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Esophagogastric Cancer Surgery During Eight Years of Surgical Auditing by the Dutch Upper Gastrointestinal Cancer Audit (DUCA)

Abstract: Objective: To evaluate changes in treatment and outcomes of esophagogastric cancer surgery after introduction of the DUCA. In addition, the presence of risk-averse behavior was assessed. Summary of Background Data: Clinical auditing is seen as an important quality improvement tool; however, its long-term efficacy remains largely unknown. In addition, critics claim that enhancements result from risk-averse behavior rather than positive effects of auditin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 32 publications
(92 reference statements)
2
59
1
Order By: Relevance
“…Dutch leakage rates are relatively high due to the historical preference for a transhiatal approach with a cervical anastomosis (associated with higher leakage rates than intrathoracic anastomoses) and the transition in recent years towards minimally invasive surgery (31% in 2011 to 93% in 2019), transthoracic surgery (43% in 2011 to 83% in 2019), and intrathoracic anastomosis (11% in 2011 to 58% in 2019). 10 As shown by a recent Dutch study, implementation of such new techniques and the associated proficiency gain curves are correlated with an increase in complications. 34 The current study showed lower (severe) postoperative complication, technical complication, and anastomotic leakage rates in centers with an annual esophagectomy volume over 40.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dutch leakage rates are relatively high due to the historical preference for a transhiatal approach with a cervical anastomosis (associated with higher leakage rates than intrathoracic anastomoses) and the transition in recent years towards minimally invasive surgery (31% in 2011 to 93% in 2019), transthoracic surgery (43% in 2011 to 83% in 2019), and intrathoracic anastomosis (11% in 2011 to 58% in 2019). 10 As shown by a recent Dutch study, implementation of such new techniques and the associated proficiency gain curves are correlated with an increase in complications. 34 The current study showed lower (severe) postoperative complication, technical complication, and anastomotic leakage rates in centers with an annual esophagectomy volume over 40.…”
Section: Discussionmentioning
confidence: 97%
“…Outcomes, like shortterm mortality and surgical radicality, improved over this time period. 10 However, it remains unknown whether these improvements are caused by centralization and whether currently (ie, with a volume threshold of 20) there still is a volume trend in clinical outcomes and if this trend eventually reaches a plateau. 11 The Dutch Upper Gastrointestinal Cancer Audit (DUCA) aims to improve Dutch esophagogastric cancer surgery by providing clinicians with benchmarked outcome feedback.…”
mentioning
confidence: 99%
“…Additionally, the anastomotic leakage rate of 18% following esophagectomy in the Netherlands is relatively high compared to other countries, an explanation is the learning curve for new techniques (e.g., minimally invasive) in recent years. Around 2010 minimally invasive surgery was introduced and many surgeons changed from a McKeown to an Ivor Lewis technique 38 . Furthermore, both clinically and radiologically proven anastomotic leakages were included.…”
Section: Discussionmentioning
confidence: 99%
“…Around 2010 minimally invasive surgery was introduced and many surgeons changed from a McKeown to an Ivor Lewis technique. 38 Furthermore, both clinically and radiologically proven anastomotic leakages were included. Finally, all patients included in this study were selected to be fit for surgery by expert opinion preoperatively, leading to allocation bias.…”
Section: Gastric Carcinomamentioning
confidence: 99%
“…Especially in countries where hospital resources are comparable, it should not matter in what hospital a patient is being treated and every hospital should be able to perform up to the standard of the best-performing center. Disclosing and safe-sharing hospital results and discussing these outcomes with other surgeons has proven to be an effective tool towards quality improvement on a national level [ 87 ].…”
Section: Postoperative Outcomementioning
confidence: 99%